Framework of educational building design for children with autism in Malaysia / Nurul Aida Nazri - Nazri, Nurul Aida (2016)
Malaysia has been actively involved in providing accessibility in term of facilities for disabled since the country ratified the Convention on the Right of the child (CRC) in 1995. Consequently, of its obligation under the CRC, Malaysia enacted few laws regarding person with disabilities which include autism under the category of learning disabilities. Nevertheless, there are no policies or guidelines which focus merely on autism in Malaysia eventhough the prevalence of autism has face a major rise. With regard to this matter, research has proven that the quality of educational building enormously affects learning outcomes of individuals. By understanding the mechanism of this disorder and needs, learning environment maybe design favourably to enhance the learning performance. Therefore, the aim of this research is to propose a Framework of Educational Building Design for Children with Autism in'Malaysia. In order to achieve the aim of research, this study utilises three objectives which are to explore the gap of the existing policy pertaining to children with autism with regards to educational building design, to identify variables in order to enhance learning environment within the context of educational building design as well as to conceptualize the variables of the learning environment in order to establish a framework. Qualitative research method has been embarked in this research whereby empirical data has been collected via semi-structured interview. Twenty-five respondents have participated in the semi-structured interviews and the data were analysed via NvivolO software. This research indicated that there is insufficient government policies been established pertaining to educational building design for children with autism in Malaysia. Yet, there are no specific building codes or policies that can be referred in order to fulfill the requirement of educational building design for children with autism because most of the building codes and policies are restricted to person with disabilities. Responses and recommendations were collected from each respondent on the key issues that were addressed in this research. Hence, the qualitative analyses were contextualized to develop a framework of educational building design for children with autism in Malaysia.